ONLINE MEDIA EXPOSURE AND CONTENT MARKETING AFFECTING DECISION - MAKING ON USING THE ELECTRONIC COMMERCE PLATFORM LAZADA - Chulawan, Chatcharin; Sasithanakornkaew, Saranthorn; Apisuphachok, Warapan (Journal of MCU Nakhondhat, 2024)
This research aims to: 1) Study the differences in the demographic characteristics and decision-making on using the e-commerce platform Lazada. 2) Study the relationship between online media exposure and decision-making on using the electronic commerce platform Lazada. 3) Study the relationship between content marketing and decision-making on using the electronic commerce platform Lazada. 4) Study the influence of online media exposure and content marketing on decision - making on using the electronic commerce platform Lazada. The study population consists of individuals who have previously used the electronic commerce platform Lazada, aged 18 and above. This is a quantitative research utilizing questionnaires as data collection tools. Statistical analysis includes frequency, percentage, mean, standard deviation, t - test, One - Way ANOVA, Pearson correlation coefficient, and Multiple Regression Analysis (MRA). The results of hypothesis testing reveal the researchers sampled a total of 400 individuals, predominantly female, aged between 18 - 28 years old, holding bachelor's degrees, with a monthly income ranging from 15,000 to 25,000 Baht, and employed as private company employees or workers. that sample groups with different ages, incomes, and occupations make different decision-making on using the electronic commerce platform Lazada. However, sample groups with different genders and education levels make similar decision-making on using the electronic commerce platform Lazada. Additionally, online media exposure and content marketing are correlated with decision-making on using the electronic commerce platform Lazada, and online media exposure and content marketing influence decision-making on using the electronic commerce platform Lazada.